PEMBUATAN MESIN MILLING PAPAN PCB - Arief Triadi; Sateria, Angga; Aswin, Fajar (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
In traditional PCB layout creation, copper solvent materials like ferric chloride are commonly used along with other processes. This final project focuses on developing a PCB (Printed Circuit Board) milling machine. The machine is designed to engrave electronic circuit layouts onto PCB boards using a CNC (Computer Numerical Control) system. The CNC machine facilitates the precise engraving of circuit layouts on PCB boards. The development of this machine involves several stages, including the design process, hardware assembly, and mechanical system assembly. The machine's control system is operated using an Arduino Mega and RAMPS 1.4, which manage the machine's movements. The machine is equipped with three stepper motors, named Nema 17, which drive the machine along three axes: X, Y, and Z. The CNC machine utilizes a single lip cutter as the engraving tool on the PCB, positioned along the Z-axis. Based on the test results for a 10 mm movement on the X, Y, and Z axes, the average movement deviation was found to be 10.23 mm for the X-axis, 10.59 mm for the Y-axis, and 10.45 mm for the Z-axis.